Exploring the benefits and types of plyometric training in volleyball: A systematic review - Hamdi, Liwa Ul; Gazali, Novri (Universitas Majalengka, 2024)
Over the past decade, research to explore the benefits and types of plyometric exercises in volleyball has grown rapidly. However, the literature review on this topic is still very limited. The aim of this study was to conduct a systematic and in-depth review of the benefits and types of plyometric exercises in volleyball. Two databases (Scopus and Web of Science) were used to select articles containing information on this topic. The search was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. After exclusion criteria, only 25 articles were categorized. Demonstrated the positive impact of various plyometric exercises on volleyball play. The results showed that the benefits and types of plyometric exercises can increase strength, agility/speed in volleyball games. In-depth analysis of the technical and tactical aspects of volleyball games shows that jumping exercises on water, jumping exercises on sand, squat jumping exercises, and vertical jumping exercises can increase leg muscle strength so that it can increase the jump height of the players to improve the stroke, especially in the smash technique (attack) in volleyball games.